EFEKTIVITAS BI’AH LUGHAWIYAH UNTUK KELANCARAN KALAM ARAB MAHASISWA KELAS KHUSUS PKPBA UIN MAULANA MALIK IBRAHIM MALANG - Indriana, Nilna; Eka Diantika, Devi (At-Tuhfah : Jurnal Studi Keislaman, 2022)
This paper aims to determine Maulana Malik Ibrahim State Islamic University (Maliki) Malang, is one of the pioneers of Arabic-language campuses that teaches Arabic intensively to its students. Until now, the existence of Arabic language learning on campus still exists and is considered successful by various universities both at home and abroad. This is inseparable from the hard work carried out by an academic support unit called PKPBA (Arabic Language Development Special Program). PKPBA was formed by the University as a strategic force in teaching and developing Arabic which will later also support the realization of a scientific structure oriented towards the integration of Islam and science. In this study, the data source used was oral data. the recording of daily conversations of special class PKPBA students at the State Islamic University of Maulana Malik Ibrahim Malang. And also data from direct interviews with informants. As a result, There are various ways to support students' fluency in language at the State Islamic University of Maulana Malik Ibrahim Malang, one of which is: The Arabic language environment (Bi'ah Lughawiyah) is an environment where Arabic is used daily to communicate with each other. No other language is used to communicate except Arabic. An environment like this will make someone quickly master speaking Arabic fluently and correctly. In a language environment, they are forced to speak and get rid of the fear of being wrong in language. The fear of being wrong in the language will hinder the fluency and success of the language itself.